Identity and lifelong learning in higher education - Gammel, Jo Ann; Motulsky, Sue; Rutstein-Riley, Amy (I am what I become : constructing identities as lifelong learners, 2020)
Learning and identity development are lifetime processes of becoming. The construction of self, of interest to scholars and practitioners in adult development and adult learning, is an ongoing process, with the self both forming and being formed by lived experience in privileged and oppressive contexts. Intersecting identities and the power dynamics within them shape how learners define themselves and others and how they make meaning of their experiences in the world. I Am What I Become: Constructing Identities as Lifelong Learners is an insightful and diverse collection of empirical research and narrative essays in identity development, adult development, and adult learning. The purpose of this series is to publish contributions that highlight the intimate connections between learning and identity. Our aim is to promote reflection and research at the intersection of identity and adult learning at any point across the adult lifespan and in any space where learning occurs: in school, at work, or in community.The series aims to assist our readers to understand and nurture adults who are always in the process of becoming. Adult educators, adult development scholars, counselors, psychologists, and sociologists, along with education and training professionals in formal and informal learning settings, will revel in the rich array of qualitative research designs, methods, and findings as well as autobiographies and narrative essays that transform and expand our understanding of the lived experience of people both like us and unlike us, from the U.S. and beyond.Volume One, Identity and Lifelong Learning in Higher Education, contains chapters by and about post-secondary educators and students. Together these chapters enhance our understanding of the inextricable link between learning and identity.